2023
DOI: 10.5312/wjo.v14.i6.458
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of patient specific vs conventional instrumentation for total knee arthroplasty: A systematic review and meta-analysis

Isobel M Dorling,
Lars Geenen,
Marion J L F Heymans
et al.

Abstract: BACKGROUND Over the past years, patient specific instrumentation (PSI) for total knee arthroplasty (TKA) has been implemented and routinely used. No clear answer has been given on its associated cost and cost-effectiveness when compared to conventional instrumentation (CI) for TKA. AIM To compare the cost and cost-effectiveness of PSI TKA compared to CI TKA. METHODS A literature search was performed in healthcare, economical healthcare, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Additionally, the surgeon’s CT-based implant plan aligned within one size of the utilized implant 100% of the time for both tibial and femoral components. On a per-case basis, PSI systems may offer cost savings related to implants compared with the overall institutional cost for standard TKA, owing to reduced instrument preparation for only the same size and one size smaller components [ 22 ]. The PSI approach also saves surgical time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the surgeon’s CT-based implant plan aligned within one size of the utilized implant 100% of the time for both tibial and femoral components. On a per-case basis, PSI systems may offer cost savings related to implants compared with the overall institutional cost for standard TKA, owing to reduced instrument preparation for only the same size and one size smaller components [ 22 ]. The PSI approach also saves surgical time.…”
Section: Discussionmentioning
confidence: 99%
“…While PSI is garnering increasing scientific and practical interest, numerous authors have reported improved alignment and component positioning [ 23 , 24 ]. According to Dorling et al [ 22 ], when considering the total cost per patient case, PSI TKA is more expensive than conventional instrumentation TKA. This higher cost is attributed to the imaging and production expenses associated with PSI TKA, despite it being less expensive than conventional instrumentation TKA in terms of mean operating room time, associated costs, and tray sterilization per patient case.…”
Section: Discussionmentioning
confidence: 99%